HUBUNGAN KECERDASAN NUMERIK DAN MINAT BELAJAR TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Sofia Nurul Hikmah (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2021)
The purpose of this study was to determine the effect of numerical intelligence on students' mathematical reasoning abilities, to determine the effect of interest in learning on students' mathematical reasoning abilities, to determine the influence of numerical intelligence and interest in learning on students' mathematical reasoning abilities. The method used in this study is quantitative with a correlation approach. The sample in this study were students of SMPN 13 Pesawaran class VIII who were randomly selected as many as 28 students. The instruments in this study were test and non-test instruments. The test instrument was used to measure students' numerical intelligence and mathematical reasoning in the form of 5 questions. The non-test instrument was used to measure students' interest in learning which consisted of 24 statements adopted from the research of Bagas Saputro (2017). Data were analyzed using simple correlation and multiple correlation. The results showed that; 1) There is no significant relationship between interest in learning and students' mathematical reasoning; 2) there is a significant relationship between numerical intelligence and students' mathematical reasoning; 3) there is a simultaneous relationship between interest in learning mathematics and numerical intelligence on mathematical reasoning, with a contribution of 68.4%.Keywords: Numerical intelligence, interest in learning, mathematical reasoning ability